White children's empathy‐related responding and prosocial behavior toward White and Black children. Issue 1 (12th August 2022) - Spinrad, Tracy L.; Eisenberg, Nancy; Xiao, Sonya Xinyue; Xu, Jingyi; Berger, Rebecca H.; Pierotti, Sarah L.; Laible, Deborah J.; Carlo, Gustavo; Gal‐Szabo, Diana E.; Janssen, Jayley; Fraser, Ashley; Xu, Xiaoye; et al.
Abstract: Relations among White (non‐Latinx) children's empathy‐related responding, prosocial behaviors, and racial attitudes toward White and Black peers were examined. In 2017, 190 (54% boys) White 5‐ to 9‐year‐old children ( M = 7.09 years, SD = 0.94) watched a series of videos that depicted social rejection of either a White or Black child. Empathy‐related responses, prosocial behaviors, and racial attitudes were measured using multiple methods. Results showed that younger children showed less facial concern toward Black than White peers and greater increases with age in concern and prosocial behaviors (sharing a desirable prize) for Black, compared to White, targets. Children's facial anger increased with age for White but not Black targets. The findings can extend our understanding children's anti‐racism development.